COMPARISON OF BIPOLAR ELECTROCAUTRY AND COLD STEEL DISSECTION METHODS FOR TONSILLECTOMY: Tonsillectomy - Ali, Muhammad; Rafique, Atif; Dastgir, Majid; Rashid, Muhammad; Maqbool, Shahzad; Bashir, Sheraz (Pakistan Armed Forces Medical Journal, 2014)
Objectives: To compare the efficacy and post-operative morbidity of bipolar electrocautry and cold steel dissection methods for tonsillectomy in pediatric population, in terms of operating time, peri-operative blood loss, post-operative pain and frequency of secondary hemorrhage.Study Design: Randomized controlled trial.Place and Duration: This study was conducted at department of ENT, Combined Military Hospital Kharian and Lahore between Jan 2009 to Jan 2012.Patients and Methods: Total 146 patients between age 6 to 12 years were enrolled in this study but only 102 patients who fulfilled the desired criteria and had regular follow up were placed in two groups. They were divided into two equal groups of 51 each labeled as A and B. Patients in group A were operated for tonsillectomy by bipolar electrocautry while group B underwent tonsillectomy by cold steel dissection method. All patients in both groups were assessed for operating time, peri-operative blood loss, secondary hemorrhage and postoperative pain on Visual Analogue Score.Results: In group A there were 27 males and 24 females while group B had 28 females and 23 males. Mean age of patients was 9.4 (SD ± 2.67) years. Patients in groups A had statistically significant lower operative time and blood loss than group B. While initial post-operative pain was not different in two groups. However late onset pain (pain on 7th and 14th day) and frequency of secondary hemorrhage was significantly higher in group A.Conclusion: Bipolar electrocautry dissection method of tonsillectomy is better than cold steel dissection method in terms of operating time and peri-operative blood loss. Although initial post-operative pain was not much significant in two groups but incidence of late onset pain and secondary hemorrhage is higher in bipolar electrocautry group.